Membrane based purification of hydrogen system (MEMPHYS). (17th May 2019) - Schorer, Linda; Schmitz, Sven; Weber, Alexandra
Abstract: A hydrogen purification system based on the technology of the electrochemical hydrogen compression and purification is introduced. This system is developed within the scope of the project MEMPHYS. Therefore, the project, its targets and the different work stages are presented. The technology of the electrochemical purification and the state of the art of hydrogen purification are described. Early measurements in the project have been carried out and the results are shown and discussed. The ability of the technology to recover hydrogen from a gas mixture can be recognized and an outlook into further optimizations shows the future potential. A big advantage is the simultaneous compression of the purified hydrogen up to 200 bar, therefore facilitating the transportation and storage. Highlights: A hydrogen purification system based on the electrochemical principle is introduced. For a gas mix with 80% hydrogen more than 99% of the hydrogen can be recovered. The potential of simultaneous purification and compression is huge.